Lexical bundles in non-native learner corpora - Engku Ibrahim, Engku Haliza (Journal of Critical Reviews, 2020)
Research has indicated that learner’s successful assimilation of lexical bundles is one of the indicators of writing competency. Additionally, literature has also shown that different types of writing require different types of lexical bundles and it is essential that learners are able to differentiate between personal stance bundles and those of academic prose. As such, this study intends to investigate the grammatical structures of frequently used lexical bundles and as well as find out if there is a difference in frequency of use of lexical bundles in different types of essays. The data were collected from 50 graphic-oriented essays and 50 open-ended essays of upper-intermediate English language learners. An analysis of the data in this study, among others, showed that our learners used less structural classifications in open-ended essays when compared to graphicoriented essays. Finally this paper presents discussions of the pedagogical implications drawn from the analysis of the data presented.